Colorimetric and fluorogenic signalling of fluoride ions by diketopyrrolopyrrole-based chemosensor1. Issue 29 (27th April 2015) - Yang, Xiaofeng; Zhang, Gege; Li, Yexin; Liu, Zheng; Gong, Xiaoqian; Gao, Bin; Zhang, Guangyou; Cui, Yu; Sun, Guoxin
<x xml:space="preserve">Abstract</x> A new colorimetric and on–off fluorescence sensor based on diketopyrrolopyrrole (DPP) was synthesized for detection of fluoride anion.